2019
DOI: 10.1177/1534484319842992
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Trust Within Organizations and Performance: A Systematic Review

Abstract: The concept of trust within organizations, or intra-organizational trust, has been considered as a potential mechanism to increase performance and as such, has attracted growing interest in the organizational literature. However, despite the increasing number of studies examining the relationship between intra-organizational trust and performance, this apparently positive link has not been consistently confirmed by empirical research, and a deeper understanding is called for. Moreover, the literature on the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 117 publications
(202 reference statements)
2
26
0
1
Order By: Relevance
“…In an organizational context, trust is an effective predictor of positive attitudes and behavior of employees [64]. The results of previous research indicate that interpersonal trust positively influences the effectiveness and performance within an organization [65], commitment [66], collaboration [67], improving organisational loyalty [68], resistance to change and reduced stress levels [69] and a decrease in employee turnover [70]. In addition, trust activates the learning process by generating social relationships using different communication channels [71].…”
Section: The Mediating Role Of Trust In Building Job Satisfactionmentioning
confidence: 99%
“…In an organizational context, trust is an effective predictor of positive attitudes and behavior of employees [64]. The results of previous research indicate that interpersonal trust positively influences the effectiveness and performance within an organization [65], commitment [66], collaboration [67], improving organisational loyalty [68], resistance to change and reduced stress levels [69] and a decrease in employee turnover [70]. In addition, trust activates the learning process by generating social relationships using different communication channels [71].…”
Section: The Mediating Role Of Trust In Building Job Satisfactionmentioning
confidence: 99%
“…Over a period of eight years, they found that organizational attitudes (i.e., job satisfaction and satisfaction with job security) predicted financial performance (i.e., ROA). In the systematic review done by Guinot and Chiva [ 17 ], they found that a significant number of studies confirmed a positive direct effect of vertical trust on job performance, although non-significant effects were also found for concrete contexts (e.g., non-Western cultures), specific measures of job performance (e.g., extra-role performance), and some types of subordinates and leaders. This systematic review concluded that there is a lack of empirical analysis of the mediating role that vertical trust plays in the team’s and organizational performance, and that future studies should continue to analyze the differences in this direct relationship according to the leadership referent of trust (i.e., trust in top leaders, like in the current study).…”
Section: Theories and Hypothesesmentioning
confidence: 99%
“…Finally, although there is not much research on trust as a psychological mechanism that explains cross-levels effects between antecedents and consequences of trust [ 17 ], based on social exchange theory, we could expect that higher levels of healthy organizational practices positively influence employees’ levels of trust in their top management (vertical trust) which in turn enhance team performance. In addition, these practices could also influence horizontal trust, and in turn, enhance team performance too (as a way of showing reciprocity).…”
Section: Theories and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, organizational HRD culture encompasses OD, T&D, CD, coaching, and related activities, all of which include critical organizational outcomes of performance and learning (Swanson & Holton, 2009). Performance is most often described to be multilayered whereby organizations measure the degree they accomplish their goals effectively and efficiently at the individual, team, organizational, and external stakeholder levels (Guinot & Chiva, 2019). Learning, on the other hand, aims to enable employees to deal with the challenges of the daily tasks (Sparr, Knipfer, & Willems, 2017).…”
Section: Introductionmentioning
confidence: 99%